Education: Hope in the Midst of Poverty - Riska Hasanah (International Journal of Educational and Life Sciences, 2023)
This paper describes poverty status and condition in East OKU regency, South Sumatera. Living in poverty will make it difficult for a person to acquire quality education and often even prevent a person from accessing education. This leads to low productivity, which leads to poverty. This reciprocal relationship is often referred to as the vicious cycle of poverty or the poverty cycle. In fact, according to scholars, education is considered as one of the strategies that can overcome the problem of poverty. This paper also explores the constraints faced by the students to continue their education and provide education strategies to reduce poverty.